Respuesta :

Answer:

x= -1  

y= 2

Step-by-step explanation:

Answer:

  (x, y) = (-1, 2)

Step-by-step explanation:

Substitution is easier if you already have an expression for the variable you want to make a substitution for. Here, we don't have that, but we have an equation with x having a coefficient of 1. We can use that to write an expression for x:

  x = 3 -2y . . . . . subtract 2y from both sides of the second equation

  5(3 -2y) +3y = 1 . . . . substitute for x in the first equation

  15 -10y +3y = 1 . . . . . eliminate parentheses

  -7y = -14 . . . . . . . . . . subtract 15, collect terms

  y = 2 . . . . . . . . . . . . . divide by -7

Use this value in the equation for x:

  x = 3 -2(2)  = -1

The solution is (x, y) = (-1, 2).